The Comparison Of Physical Capacities, In-Game Activity Profiles And Decision-Making Skills Of Football Referees According To Their Experience Level - Halil İbrahim Ceylan; Özcan Saygın; Hakan Karabalcık (Selcuk University, 2020)
The aim of this study was to compare the physical capacities, in-game activity profiles and decision-making skills of experienced and less experienced football referees during the match. A total of 10 football referees, 5 experienced ( gt;5 years) and 5 less experienced ( lt;5 years) participated in this study voluntarily. As a result of statistical analysis; aerobic capacity of experienced referees (61.14±3.31 ml/kg/min) was significantly higher than less-experienced referees (54.67±2.93 ml/kg/min.) (p lt;0.05). As compared with less-experienced referees (9.09±1.08 km), the total distance covered (10.73±.41 km) and sprint distance of experienced referees (experienced: 686.95±140.93 m, less-experienced: 459.85±168.37 m) were significantly higher in the match. There was no significant difference in the total decision scores in two football competitions between experienced and less experienced referees (184.80 ± 21.25 and 193.40±26.12) (p gt;0.05). It was found that less-experienced referees made more incorrect decisions in the match than experienced referees (9.60±4.21 and 20.20±2.68) (p lt;0.05). Experienced referees had higher in-game activity profiles than less-experienced referees, and their incorrect decision making scores were lower. In addition, in order to minimize the incorrect decision scores of the experienced and especially less-experienced referees in the match, it is thought that it is important to include exercises related to perceptual-motor skills in training programs as well as physical training.